Notalgia Paraesthetica - Malakar Subrata; Dhar Sandipan (Wolters Kluwer Medknow Publications, 1998)
Two cases of notalgia paraesthetica (NP) are presented. Both the patients were female and above 30 years of age. Clinically the lesions closely simulated macular amyloidosis over interscapular region. However, history of associated pruritus, tingling, fornication and altered sensation over the patch pointed towards the diagnosis of NP, Histopathological examinations in both the cases revealed intraepidermal necrotic keratinocytes with desquamation remnants of necrotic keratinocytes in the stratum corneum. Congo red and crystal violet stains were negative for presence of amyloidal in thedermis. In both the patients, symptomatic improvement was observed after 3 weeksâ€ application of topical capsaicin.